The global evolution of talent promotion within Olympic sports: A focus on the national systems and contribution of the former German Democratic Republic, Australia, and the United Kingdom - Weissensteiner, Juanita R. (Frontiers in Sports and Active Living, 2023)
In this chapter we chronicle and explore the global evolution of national level talent promotion through the lens and respective journeys of the former German Democratic Republic, Australia and the United Kingdom. Whilst ideologically vastly different, core elements of talent promotion were mirrored and extended within the next national iteration. Key learnings obtained from this historical and comparative exploration serve to provide excellent learnings for policy makers, strategists, practitioners and researchers to support the review and development of current and future national talent promotion systems.